Eddies in the North Greenland Sea and Fram Strait From Satellite Altimetry, SAR and High‐Resolution Model Data. Issue 7 (24th June 2020) - Bashmachnikov, Igor L.; Kozlov, Igor E.; Petrenko, Larisa A.; Glok, Natalia I.; Wekerle, Claudia
Abstract: In this study, we investigate eddy dynamics in the northern Greenland Sea and the Fram Strait using AVISO altimetry, spaceborne synthetic aperture radar (SAR), and Finite Element Sea ice‐Ocean Model (FESOM) high‐resolution numerical model data. In the region, eddies are thought to play an important role in the redistribution of the warmer and saltier Atlantic Water between the Arctic Ocean and the areas of deep convection in the central Greenland Sea. We found that eddies detected in AVISO and in SAR form two complementary data sets of large mesoscale eddies (with typical radii of 30–50 km) and of small mesoscale/submesoscale eddies (with typical radii of 1–5 km and not exceeding 30 km), respectively. For large mesoscale eddies, the number of cyclones and anticyclones is approximately the same, while for submesoscale eddies, cyclones are strongly dominating. The limitations and possible biases in each of the data sets are discussed and cross‐validated against FESOM results. It is noted that the most energetic eddies are concentrated along the major currents and in the northern part of the region. Eddy translations follow the mean currents in their overall cyclonic circulation around the northern Greenland Sea. A convergence of the eddies toward the Nordbukta area is detected. On seasonal time scale, a higher number of more intense mesoscale eddies is observed during winter, associated with a quasi‐simultaneous intensification of the mean currents. Model results also show an increase in the number of small eddies in spring‐early summer attributed to the decay of large eddies, while in late autumn, the opposite tendency suggests eddy merger. Plain Language Summary: Ocean eddies in the northern Greenland Sea and the Fram Strait play an important role in the redistribution of the northward fluxes of heat and salt between the Arctic Ocean and the Greenland Sea. In spite of their climatic importance, there is a very limited number of in situ and infrared/ocean color remote sensing observations in the region, which is due to severe weather conditions and frequent sea ice/cloud cover. In this study, we present the results of eddy detection using two weather‐independent remote sensing data sources: satellite altimetry and synthetic aperture radar (SAR). We have shown limitations of the data sets, each of which provides a complementary information on large mesoscale eddies (altimetry) and on predominantly submesoscale eddies (SAR). The results are cross‐validated against Finite Element Sea ice‐Ocean Model (FESOM) high‐resolution numerical model results. In spite of the noted difference, all data sets show similar spatial statistics of eddy properties. We found an increase of eddy number and intensity toward the mean currents. On seasonal time scale, mesoscale eddies are the most effectively generated in winter. In spring‐early summer, the increase in a relative number of smaller eddies (FESOM results) suggests the dominance of large eddy decay processes, while in late autumn, the opposite tendency suggests eddy merger. Key Points: First cross‐validation of the number/properties of eddies in satellite altimetry and SAR images is obtained over the North Greenland Sea Spatial patterns of eddy properties in SAR, AVISO, and FESOM data are similar, though eddy radii in SAR are much smaller than in AVISO The most energetic eddies were found to follow the main topographic features and accumulate in the Nordbukta area